Primary cutaneous plasmablastic lymphoma revealing clinically unsuspected HIV infection - Marques, Silvio Alencar [UNESP]; Fernandes Abbade, Luciana P. [UNESP]; Guiotoku, Marcelo Massaki; Marques, Mariangela Esther Alencar [UNESP] (FapUNIFESP (SciELO), 2016)
Plasmablastic lymphoma is a rare subtype of diffuse large B-cell lymphoma more frequently diagnosed in immunosuppressed patients, mainly HIV-infected. Primary cutaneous plasmablastic lymphoma is extremely rare, and in this patient it was the first clinical manifestation of unsuspected HIV-infection.
Keywords: AIDS-related; HIV infections; Lymphoma; Skin neoplasms